Teoria da gravidade escalar geométrica interpretada sob a perspectiva do modelo de dimensões extras - Gomes, Fernando Oliveira da Silva (2018)
This thesis consists in a review of some aspects of the General Theory of Relativity and of the Classical Field Theory, in order to study a paper from a group of researchers form ICRA - CBPF which presents an alternative theory of gravity. In this theory, gravity is a geometric effect, like in General Relativity, but the curvature of spacetime is characterized by a function of a scalar field. In other words, the gravity would have only one degree of freedom, instead of ten as in General Relativity. After this study, it is shown how the geometric scalar theory of gravity can be interpreted in a new and not yet explored way: as a representation of a four-dimensional surface imbeded in a five-dimensional spacetime, allowing the study of the geometric scalar gravity in the brane world model.